2015
DOI: 10.1016/j.vetpar.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus infections in the Baltic region

Abstract: In the Baltic countries, the two zoonotic diseases, alveolar echinococcosis (AE) caused by Echinococcus multilocularis, and cystic echinococcosis (CE) caused by Echinococcus granulosus, are of increasing public health concern. Observations from Estonia, Latvia and Lithuania indicate that the distribution of both parasites is wider in the Baltics than previously expected. In this paper, we review and discuss the available data, regarding both parasitoses in animals and humans, from the Baltic countries and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…), such as the tapeworms Echinococcus granulosus and E. multilocularis (e.g. Moks et al., ; Marcinkute et al., ) that cause the potentially fatal diseases cystic and alveolar echinococcosis, respectively. Using questionnaires, regular Europe‐wide studies should be initiated to investigate public attitudes.…”
Section: Suggestions For Science‐based Wolf Conservation and Managemementioning
confidence: 99%
“…), such as the tapeworms Echinococcus granulosus and E. multilocularis (e.g. Moks et al., ; Marcinkute et al., ) that cause the potentially fatal diseases cystic and alveolar echinococcosis, respectively. Using questionnaires, regular Europe‐wide studies should be initiated to investigate public attitudes.…”
Section: Suggestions For Science‐based Wolf Conservation and Managemementioning
confidence: 99%
“…One example of this may be the cestode Echinococcus multilocularis, which has a well-described life cycle, frequently including rodent species as intermediate hosts and foxes as definitive hosts. In parts of northern Europe, including Estonia and the other Baltic states, foxes frequently consume rodents, and the current prevalences of Echinococcus multilocularis in red foxes are among the highest recorded (30-60%; Moks et al 2005, Marcinkute et al 2015, Laurimaa et al 2016. In such areas, infection might be expected to decline if rodent consumption declines over time.…”
Section: The Ecosystem Role Of Red Foxes In the Face Of Global Changementioning
confidence: 99%
“…In fact, until the 1990s, only a ‘core’ area consisting of Eastern France, southern Germany, parts of Switzerland and Austria were known to be endemic for the disease [5]. More recently, the expansion of the parasite into several new areas such as the Baltic regions, Denmark, the Netherlands, Poland, Romania, Slovakia, Slovenia and the increase of human AE incidence in ‘core’ areas such as Austria, France and Switzerland, suggested that the disease was spreading in Europe and the incidence of human AE increasing at least in some regions [610]. Although greater awareness and the use of advanced diagnostic tools may have contributed to an improvement in the detection of E. multilocularis infection in animals and humans, epidemiological research conducted over the past 20 years, suggested the expansion of this parasite in European countries [9].…”
Section: Introductionmentioning
confidence: 99%